Campus security practices of Philippine College of Science and Technology - Mabanglo, Jamaica Kim Lopez (Panpacific University : [s.n.], 2018)
The objective of this study is to determine the campus security practices of Philoppine College of Science and Technology, specifically, it sought to determine the level of implementation of campus security in (PhilCST) as perceived by the respondents along: (a) physical security (b) document security (c) personnel security; to determine if there is a difference in the level of implementation as perceived by the four groups of respondents; to determine the campus security measures along the three major areas of security by PhilCST as perceived by the four group of respondents; and to determine if there is a difference on the campus security measures along the three major areas of security by PhilCST as perceived by the four groups of respondents.
Bibliography: pages 111-117.
CHED-La Union
Keywords: Securities -- School